Transcriptional activation of MdDEF30 by MdWRKY75 enhances apple resistance to Cytospora canker - Hongchen Jia; Youwei Du; Yuanyuan Liu; Shuanghong Wang; Yan Wang; Sadia Noorin; Mark L. Gleason; Rong Zhang; Guangyu Sun (Journal of Integrative Agriculture, 2025)
Defensin, an essential component of plant development, is indispensable in pathogen resistance. However, the molecular function of defensins under pathological conditions of Cytospora canker has not been characterized in apple plants. The present study exhibits a detailed overview of the phylogeny and structure of 29 defensins (MdDEF) in apple. Expression analysis revealed that MdDEF genes were spatiotemporally diverse across apple tissues. Five MdDEF genes were found to be significantly up-regulated following a challenge with Cytospora mali. The transgenic overexpression of five defensin genes in apple calli enhanced resistance to C. mali. Among them, MdDEF30 was strongly induced and conferred the highest resistance level in vivo. Meanwhile, antifungal activity assays in vitro demonstrated that a recombinant protein produced from MdDEF30 could inhibit the growth of C. mali. Notably, MdDEF30 promoted the accumulation of reactive oxygen species (ROS) and activated defense-related genes such as PR4, PR10, CML13, and MPK3. Co-expression regulatory network analysis showed that MdWRKY75 may regulate the expression of MdDEF30. Further yeast one-hybrid (Y1H), luciferase, and chromatin Immunoprecipitation quantitative polymerase chain reaction (ChIP-qPCR) assays verified that MdWRKY75 could directly bind to the promoter of MdDEF30. Importantly, pathogen inoculation assays confirmed that MdWRKY75 positively regulates resistance by transcriptionally activating MdDEF30. Overall, these results demonstrated that MdDEF30 promotes resistance to C. mali in apple plants and that MdWRKY75 regulates MdDEF30 expression during the induction of resistance, thereby clarifying biochemical mechanisms of resistance to C. mali in apple trees.